Para além dos contos de fadas : o teatro do oprimido como perspectiva metodológica na construção da identidade cultural da criança - Oliveira, Soraya de Souza de (2023)
The research aims to understand how Theatre of the Oppressed is configured from a methodological perspective in the reflective process of children, regarding their cultural identity and their role as readers of fairy tales, as well as their identification or strangeness towards the characters of this literary genre. It also investigates whether Theatre of the Oppressed encourages children to critically analyze fairy tales, focusing on the strangeness of character traits and situations depicted in this children’s narrative, which is laden with values and beliefs from European culture. This work has as its field of investigation the Municipal School Nazinha Barbosa da Franca, and as subjects of the research 25 children between 08 and 12 years old, members of the school’s theater group, formed since the year 2019, attending the 4th and 5th years of the initial years of Elementary School. This research addresses the Theater of the Oppressed from a historical-critical perspective, guided by the theoretical and methodological light of Augusto Boal and Paulo Freire. It is of a qualitative nature, supported by participant observation and by the exercises, games and techniques of the theater of the oppressed, it adopts as research instruments the field diary of the researcher and the students aided by the conversation circles, by the texts created by the children, audios and videos of the dynamic actions of the process, seeking to understand how the Theater of the Oppressed, as a methodological perspective, contributes to the construction of children’s cultural identity as it opposes the colonial reading of fairy tales. The children were provoked to perceive and list the themes that oppress them from the critical reflection on the characters and oppressive situations. It was concluded that the Theater of the Oppressed contributes to the construction and/or strengthening of children’s cultural identities, expressed in the poetic and aesthetic corporealities observed in the dramaturgical creations of these children, from the critical reading of fairy tales.